2008
DOI: 10.1186/1471-2466-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Post tracheostomy and post intubation tracheal stenosis: Report of 31 cases and review of the literature

Abstract: Background: Severe post tracheostomy (PT) and post intubation (PI) tracheal stenosis is an uncommon clinical entity that often requires interventional bronchoscopy before surgery is considered. We present our experience with severe PI and PT stenosis in regards to patient characteristics, possible risk factors, and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
207
1
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(234 citation statements)
references
References 38 publications
(48 reference statements)
14
207
1
12
Order By: Relevance
“…Tracheal stenosis is narrowing of the tracheal lumen from fibrosis or granulation tissue formation after intubation or tracheostomy tube placement with an incidence as high as 85% (56). Only 3-12% are clinically important and require further intervention (48).…”
Section: Complications Of Tracheostomymentioning
confidence: 99%
See 1 more Smart Citation
“…Tracheal stenosis is narrowing of the tracheal lumen from fibrosis or granulation tissue formation after intubation or tracheostomy tube placement with an incidence as high as 85% (56). Only 3-12% are clinically important and require further intervention (48).…”
Section: Complications Of Tracheostomymentioning
confidence: 99%
“…Rigid or flexible bronchoscopy with radial resection of the stenotic area with cautery knife, balloon dilation, cryotherapy, mitomycin application are possible treatment options before considering surgical resection (56).…”
Section: Complications Of Tracheostomymentioning
confidence: 99%
“…Stenosis related to intubation tube is usually greater than cannula stenosis. [21] Many studies have reported the relationship between prolonged intubation and frequency of tracheal stenosis; however, to our knowledge, no study has been conducted showing the relationship between intubation duration and stenotic segment length in the literature. According to the literature findings, the most important factor affecting resection length is the number of stenotic areas.…”
Section: Discussionmentioning
confidence: 86%
“…In a study by Zeis et al [9] the length of stenosis was 2.6 cm in postintubation stenosis compared to 3.57 cm in posttracheostomy. In our study average length of tracheal stenosis was 2.33 cm in both postintubation and post tracheostomy.…”
Section: Etiopathogenesismentioning
confidence: 90%